Behavioral aspects of the host Diatraea saccharalis produced in a laboratory (Research, Society and Development, 2021)
The expansion in the cultivation of sugar cane attracts several pest insects, representing a limiting factor to the sugarcane culture in Brazil. The objective of the research was to analyze the behavioral aspects, in laboratory, of the sugarcane borer Diatraea saccharalis as host of Cotesia flavipes. The experiment was developed in three stages, in a completely randomized way. In the first stage, corresponding to the evaluation of the biological cycle of egg-adult life, the experiment used 30 couples selected at random from the commercial creation of the laboratory, being accommodated in an individualized way. In the second stage, the viability diagnosis of larva-pupa, larva-adult and pupa-adult was carried out, as well as the sexual ratio of D. saccharalis adults. 600 larvae were collected during five weeks (120 units per week). In the third stage, in relation to the evaluations of the experiment to measure the quantity of larvae by couples, it was necessary to adopt four treatments with 10 repetitions each, using an adult insect couple per mating chamber. In all the studied phases, the results highlight that the viability of this host presents rates above 90%. In the adult sex ratio, females are the majority. During the oviposition period, the average amount of larvae obtained per couple was 243 individuals. It is concluded that temperature is an important factor to prolong or decrease the life cycle of D. saccharalis.Keywords: Sugar cane borer; Biological control; Production of beneficial insects.